Performance of Coated Carbide Tools when Turning Inconel Alloy 718 under Cryogenic Condition using RSM / N. Badroush ...[et al.] - Badroush, N.; Che Haron, C. H.; A. Ghani, J.; Azhar, M. F.; Abdul Halim, Nurul Hayati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper investigates the influence of cutting parameters on different responses variables and the performance of PVD coated carbide cutting tool when turning Inconel 718 under cryogenic condition. The factors and range of parameters investigated are; cutting speed (90-150 m/min), feed rate (0.05-0.2mm/rev) and depth of cut (0.25-0.75mm). The experimental runs were established using Box-Behnken design experiment. For the responses, 2 variables were evaluated which are surface roughness (Ra) of the machined surface and tool life (TL) of the insert. Analysis of Variance (ANOVA) was used to identify factors which significantly affect the response variables. From the analysis, the cutting speed and feed rate are the most significant factors affecting the TL followed by the depth of cut. While for the Ra, the interaction of feed rate and depth of cut are the most significant, followed by the depth of cut. The prediction Ra and TL models were developed with 95% of prediction interval between the predicted and actual experiments using the optimal parameters.